2013
DOI: 10.1074/jbc.m112.358416
|View full text |Cite
|
Sign up to set email alerts
|

The Polybasic Insertion in Autotaxin α Confers Specific Binding to Heparin and Cell Surface Heparan Sulfate Proteoglycans

Abstract: Background:The autotaxin ␣ splice variant (ATX␣) contains a unique polybasic insertion of unknown function. Results: ATX␣ binds strongly to heparin and cell-associated heparan sulfate. Conclusion: The ATX␣ insertion confers specific binding to heparan sulfate proteoglycans thereby targeting LPA production to the plasma membrane. Significance: ATX isoforms use distinct mechanisms to ensure spatially restricted LPA production and signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 49 publications
(57 reference statements)
1
48
0
Order By: Relevance
“…All ATX isoforms display similar lysoPLD activities and substrate preferences ( 55,56,59 ). ATX-catalyzed substrate hydrolysis follows simple Michaelis-Menten kinetics, with no evidence for an interfacial activation mechanism and consistent with the notion that ATX acts on free lysophospholipids in the aqueous phase.…”
Section: Atx Structure-functionsupporting
confidence: 62%
See 1 more Smart Citation
“…All ATX isoforms display similar lysoPLD activities and substrate preferences ( 55,56,59 ). ATX-catalyzed substrate hydrolysis follows simple Michaelis-Menten kinetics, with no evidence for an interfacial activation mechanism and consistent with the notion that ATX acts on free lysophospholipids in the aqueous phase.…”
Section: Atx Structure-functionsupporting
confidence: 62%
“…most likely through the Arg/Lys-rich clusters in the insertion, whereas ATX ␤ does not ( 59 ). Heparin enhanced the lysoPLD activity of ATX ␣ toward LPC up to 2-fold, but it had no detectable effect on the activity of ATX ␤ ( 59 ).…”
Section: Lpa Production and Bioavailabilitymentioning
confidence: 99%
“…The slow release of LPA, taking place in the range of tens of seconds 28 , suggested a mechanism where ATX could also act as an LPA carrier, spreading LPA signal to distal locations from those where LPC was taken. Such a model is also supported by data that show that Autotaxin can be recruited to the cell surface binding both to integrins 13,31 and surface heparin sulfate proteoglycans 32 .…”
Section: Fluorescent Probe 12-(n-methyl-n-(7-nitrobenz-2-oxa-13-diazmentioning
confidence: 65%
“…Second, it has been shown that ATX binds surface integrins through the SMB domains 13,31,38 , whereas the longer isoform of ATX (ATXα) binds to heparan sulfate proteoglycans 32 . While this binding will localize ATX at the cell surface, likely making LPA delivery to surface receptors more efficient, it cannot be excluded that it also affects the kinetics of LPC hydrolysis in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Although no specifi c differences in the core mechanism of catalysis or physiological activities between the fi ve ATX variants have yet been reported, differences in enzymatic parameters, tissue expression levels, and isoform stability have been documented ( 7 ). For instance, ATX ␤ is the most abundant isoform found in plasma ( 10 ), whereas ATX ␣ is unstable and less common in peripheral tissues due to a long polybasic cleavable insert that mediates ATX recruitment to the cell membrane through the interaction with heparan sulfate proteoglycans ( 7,11 ). The identity and functional signifi cance of factors regulating alternative splicing of exons 12 and 21, as well as the deletion of the VEPK peptide in the lasso loop, remain to be determined.…”
Section: Structure and Enzymatic Activitymentioning
confidence: 99%